Points of Vew : Readings in American Government and Politics - Robert E DiClerico; Allan S Hammock (New York McGraw-Hil, 2004)
Presents a comprehensive collection of articles on the major topics covered in American Government courses. Each topic is selected to reflect various political debates, as well as covering traditional topics of interest in American Government. It gives readers a clearer understanding of several issues in politics and government.
Include Notes
Keywords: United States -- Politics and government